БИОТЕХНОЛОГИЯ БИОПРЕПАРАТОВ И ЭЛИКСИРОВ ЖИЗНИ НА ОСНОВЕ МИКРОБНЫХ КЛЕТОК (Experimental biology, 2015)
Biotechnologies of biological products, elixirs on the basis of yeast, lactic bacteria, grain, bean, fruit-andvegetable cultures are considered. Examples of influence of new elixirs on ability to live of the person and immunityincrease are given
Keywords: biological products; immunity